Epidemiology and Survival Outcomes of Genitourinary Cancers: A Retrospective Cohort Study from Southern Saudi Arabia - Badheeb, Ahmed M.; Alkhanbashi, Omar; Alzubaidi, Qasim; Al Asmari, Abdullah; Eltohami, Doaa Abdallah; Ahmed, Faisal; Ben Yahya, Esam Ali; Alkarak, Samer; Baslasel, Omar S.; Aman, Abdelaziz; et al. (Asian Pacific Journal of Cancer Care, 2025)
Background: Genitourinary (GU) cancers represent a significant health burden in Saudi Arabia, yet region-specific data from the southern Najran region are scarce. This study aims to characterize the epidemiology and survival outcomes of GU malignancies in this understudied population. Patients and Methods: We conducted a retrospective single-center cohort study of 150 adults with histologically confirmed GU cancers (prostate [38.0%], bladder [28.7%], renal cell carcinoma [26.0%], testicular [7.3%]) treated at King Khaled Hospital, Najran, between 2014 and 2023. Demographic, clinical, and treatment data were analyzed. Overall survival (OS) was assessed using Kaplan-Meier methods. Multivariable Cox regression and propensity score matching were used to identify prognostic factors. Results: The cohort was predominantly male (85.3%) with a mean age of 64.2 years. At diagnosis, 42.0% had localized disease, 18.0% had regional involvement, and 40.0% had metastatic disease. With a median follow-up of 42 months, 98 deaths were observed. The median OS for the entire cohort was 28.4 months (95% CI: 24.1–32.7). The 5-year OS rates varied significantly by subtype: prostate, 38.5%; bladder, 47.2%; renal cell carcinoma, 51.8%; and testicular cancer, 89.3%. Multivariable analysis identified metastatic disease (adjusted hazard ratio [aHR] = 3.85; 95% CI: 2.91–5.10) and increasing age (per decade, aHR = 1.42; 95% CI: 1.21–1.67) as independent predictors of mortality. Surgical treatment was associated with a significant survival benefit (aHR = 0.52; 95% CI: 0.40–0.68), a finding confirmed in a propensity-matched analysis. Conclusions: This first comprehensive analysis from Najran reveals a high burden of advanced GU cancers and significant survival disparities. Metastatic disease and older age are key drivers of mortality, while surgical intervention is strongly associated with improved outcomes. These findings underscore an urgent need for enhanced early detection programs and optimized treatment access in this region.